Land Use Conversion Practices In Poncol Magetan Sub-District - Rizka Fitri Elawati; I. Nyoman Suluh Wijaya; Fauzul Rizal Sutikno (Publikasi Indonesia, 2023)
In maximizing the benefits of forests and forest areas for the welfare of the people, all forests and forest areas must be utilized by taking into account their nature, characteristics, and vulnerabilities, while maintaining their basic functions that cannot be changed. Land needs in Poncol District, Magetan Regency continue to increase along with population growth, and social and economic structure development. Changes in land use due to continuous development give rise to forest areas. Although spatial planning and forestry laws prohibit land use change, forest land conversion still occurs by utilizing instrumental regulations in the decision-making process. This paper aims to identify the consistency of the practical decision-making process on land use change in Alastuwo Magetan City against Law Number 41 of 1999. By taking a Grounded Theory approach, this paper uses Atlas. ti as a tool to analyze practical processes and motivation. By comparing policy and practice, the study found that incomplete documents and discussions were serious weaknesses in the practice process in Alastuwo District, Poncol District, and Magetan Regency